Design of a Manure Smelting Machine Using a 1 HP DC Electric Motor, Using a V-Belt - Sutrisno, Galih Muji Tri (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
This plan is used to create working design drawings for the construction of a reliable, durable, safe, and effective livestock dung smelter machine, as well as to get the performance test results and economic analysis of the dung smelter. There are three different ways to phrase the issue in relation to the three planning goals. The design of a livestock manure crusher machine is done in stages, including task planning and explanation, product idea planning, and design. Technical examination examines torque, power generated by the shaft, and frame design. Due to the design of a manure smelter with SOP sizes of P 107 cm, L 27 cm, and H 124 cm, an electric motor with a power capacity of 900 to 1300 watts is intended to be used for the propulsion of the animal dung crushing machine. The machine must be able to produce 300 kg per hour of driving source DC electric motor, which is equivalent to 1 horsepower. engines' power The transmission system, which uses a V-belt and a driving shaft with a diameter of 3 cm, is what powers the engine. The 2.0 mm thick plate used in the frame construction rotates at 1400 RPM and is formed of 6 mm canal iron and tubes